Analisa Resiliensi Matematik Siswa SMP pada Materi SPLDV di SMP Negeri 4 Sumbang (Mandalika Mathematics and Educations Journal, 2022)
Mathematical resilience is a positive affective trait of students when learning mathematics. This study aims to obtain an overview of the mathematical resilience of junior high school students on the SPLDV material. This study uses a qualitative descriptive research method. This research was conducted at SMP Negeri 4 Contributing by taking 30 students of class VIII as research subjects. The research subjects used were selected by purposive sampling. The instrument used is a mathematical resilience questionnaire on the material of a two-variable linier equation system. Steps in data analysis include: (1) reduction of data and categories; (2) data presentation; and (3) drawing conclusions and verification. The results showed that the VIII grade students of SMP Negeri 4 Sumbang were divided into 3 levels of mathematical resilience, namely students who had a high level of mathematical resilience had high confidence, were very easy to socialize, had high mathematical communication skills, had excellent self-control and high self-motivation; students who have a moderate level of mathematical resilience have good confidence and trust, have poor mathematical communication skills, are less able to socialize, lack self-control but still have self-motivation to correct failures; students who have low levels of mathematical resilience have low confidence, low self-motivation, have difficulty socializing, have low mathematical abilities, and have low self-control because they are easily frustrated.